Metabolic changes during pregnancy in glucose‐intolerant NZO mice: A polygenic model with prediabetic metabolism. Issue 9 (6th May 2020) - Grupe, Katharina; Asuaje Pfeifer, Melissa; Dannehl, Franziska; Liebmann, Moritz; Rustenbeck, Ingo; Schürmann, Annette; Scherneck, Stephan
Abstract: Gestational diabetes mellitus (GDM) is a complex metabolic disease involving genetic and environmental factors. Recent studies have underlined its heterogeneity, so it is reasonable to divide patients into subpopulations depending on whether an insulin secretion or sensitivity defect is predominant. Since testing for GDM is usually performed in the second trimester, misinterpretation of prediabetes as gestational diabetes may occur. As with type 2 diabetes (T2DM), rodent models are needed for both GDM and prediabetes, but few do exist. Here, we compared the metabolic changes in pregnant normal NMRI mice with those in New Zealand obese (NZO) mice. Male animals of this strain are an established model of T2DM, whereas female mice of this strain are protected from hyperglycemia and β‐cell death. We demonstrate that female NZO mice exhibited impaired glucose tolerance, preconceptional hyperinsulinemia, and hyperglucagonemia without any signs of manifest diabetes. The NZO model showed, compared with the NMRI control strain, a reduced proliferative response of the Langerhans islets during pregnancy (3.7 ± 0.4 vs. 7.2 ± 0.8% Ki‐67‐positive nuclei, p = .004). However, oral glucose tolerance tests revealed improved stimulation of insulin secretion in both strains. But this adaption was not sufficient to prevent impaired glucose tolerance in NZO mice compared with the NMRI control ( p = .0002). Interestingly, glucose‐stimulated insulin secretion was blunted in isolated primary NZO islets in perifusion experiments. In summary, the NZO mouse reflects important characteristics of human GDM and prediabetes in pregnancy and serves as a model for subpopulations with early alterations in glucose metabolism and primary insulin secretion defect. Abstract : The aim of this work was to evaluate metabolic changes during pregnancy within the polygenic NZO mouse model and if it is a suitable one for the human disease. NZO mice showed early alterations in glucose homeostasis and insulin secretion, but no overt diabetes. Interestingly, the preconceptionally impaired glucose tolerance did not deteriorate during gestation despite a proliferation defect of Langerhans islets.